Analysis of Factors Associated with the Incidence of Hypertension in Community Health Centres - Fitria Yurnia Sari; Arie Wahyudi; Lilis Suryani; Ali Harokan (Lentera Perawat, 2024)
There is still a high number of cases and there is an increase from year to year in cases of hypertension in the work area of the Community Health Center and there is a risk of uncontrolled blood pressure, causing complications in hypertensive patients. This study aims to determine the factors associated with the incidence of hypertension at the Martapura Health Center, East Ogan Komering Ulu Regency in 2024. The design of this research is quantitative with a cross-sectional approach. The sample in this study were people seeking treatment in Martapura in 2024. The sample in this study was 98 people. The sampling method uses purposive sampling. This research was carried out on February 22-March 15 2024. Data was collected using a questionnaire. Bivariate data analysis used the Chi-Square test and multivariate logistic regression. The results of the study showed that there was a relationship between age (p value 0.00), body mass index (p value 0.005), physical activity (p value 0.000), consumption of fatty foods (p value 0.011), and family history (p value 0.029) with the incidence of hypertension at the Martapura Health Center, East Ogan Komering Ulu Regency in 2024. The most dominant factor in the incidence of hypertension at the Martapura Health Center, East Ogan Komering Ulu Regency in 2024 is age (p value 0.000), (OR 0.062). The conclusion is that there is a relationship between age, body mass index, physical activity, consumption of fatty foods and family history with the incidence of hypertension at the Martapura Health Center, East Ogan Komering Ulu Regency in 2024. Suggestions for the Martapura Health Center can improve the PTM program, especially hypertension in the elderly, as well as provide education in the community to carry out routine control of hypertension status.